Effect of Partially Purified Polygalacturonase and Cellulase on Red Guava Juice Clarification at Various Incubation Times and Temperatures - Esti Widowati; Adhitya Pitara Sanjaya; Ardhea Mustika Sari; Shindy Ambarwati (agriTECH, 2021)
Red guava juice has some undesirable characteristics including high viscosity and cloudiness as well as sediment formation due to the presence of polysaccharide in the juice. Hence, enzymatic treatment for juice clarification is needed to overcome this problem. The current study was aimed to evaluate the effect of incubation times and temperature on juice clarification using partially purified polygalacturonase from Bacillus licheniformis and cellulase from Bacillus subtilis. The incubation times of 60,90, and 120 minutes and temperatures of 35 °C, 47.5 °C, and 60 °C were used in this study. pH value, total dissolved solids (TDS), transmittance, viscosity, and yield were analyzed. The results showed that incubation temperature had a significant effect on all the parameters except for pH value. The interaction between incubation temperature and time on decreasing pH value and viscosity was observed. The best clarification condition was observed at incubation time of 47.5 °C for 90 minutes, which resulted in pH, TDS, transmittance, viscosity, and yield of 4.98±0.13, 7.67±0.21 °Brix, 23.27±0.24%T, 36.37±3.46 cP, and 77.51±1.95% respectively.